Filipino sa dominyo ng kapangyarihan - Añonuevo, Roberto T. 1968- (University of Santo Tomas Publishing House, 2013)
This book talks about issues of the Filipino language from its use in the national policies and programs to the individual everyday use. The topics include orthography and the modern colloquial terms, politics and humor, textbooks and translations, and the use of the Filipino language in education, law, business and authority, while trying to make a case for new government policies on multilingualism.